Biopriming of corn seeds based on Bacillus subtilis under different storage periods (Bioagro, 2024)
Corn crop (Zea mays L.) is one of the pillars of Brazilian agriculture, with a wide cultivation area and high productivity; Brazil is the world's second largest exporter of this cereal. For this reason, the aim of the present study was to evaluate the viability of biopriming of corn seeds with a product based on Bacillus subtilis, at different concentrations, up to 120 days of storage. The research was carried out in the seed technology laboratory of the State University of Londrina (UEL), using the commercial corn seeds Balu 366. The experimental design was completely randomized, with four replications, in a 7 × 5 factorial scheme, with seven concentrations of the commercial product based on Bacillus subtilis (Serenade) for seed biopriming (0.0, 2.5, 5.0, 7.5, 10.0, 12.5, and 15.0 %) and five storage periods in a cold chamber (0, 30, 60, 90, and 120 days). The evaluation of the physiological quality of the seeds occurred through germination, cold and seedling length tests. The variables analyzed were first germination count, germination percentage, vigor from the cold test, shoot length, length of the longest root, shoot dry mass, and root dry mass. For the statistical analysis, adjustments of regression models with the best fit were made. The biopriming of seeds proved to be an advantageous practice to enhance the physiological quality of the seeds under storage; it should be carried out at a concentration of 2.5 %, due to its economic viability, considering its efficiency equivalent to the highest concentrations. The biopriming of seeds proved to be a viable practice for seed storage for up to 60 days.
Keywords: Germination; seed conditioning; vigor; Zea mays